Paediatric Cushing’s disease: long-term outcome and predictors of recurrence - Savage, Martin O.; Ferrigno, Rosario (Frontiers in Endocrinology, 2024)
Paediatric Cushing's disease (CD) is characterized by excess ACTH secretion from a pituitary adenoma, leading to hypercortisolism. It has approximately 5% of the incidence of adult CD and is a rare disorder in the paediatric age range. The four most specific presenting features of hypercortisolism are: change in facial appearance, weight gain, decreased linear growth and virilisation shown by advanced pubic hair for the stage of breast development or testicular volume. The main diagnostic priority is the demonstration of hypercortisolism followed by distinction between its ACTH-dependent and ACTH-independent origin, thus leading to identification of aetiology. All treatment options aim to resolve or control hypercortisolism. Consensus favours transsphenoidal (TSS) pituitary surgery with selective removal of the corticotroph adenoma. TSS in children with CD is now well established and induces remission in 70-100% of cases.External pituitary radiotherapy and bilateral adrenalectomy are second-line therapeutic approaches in subjects not responding to TSS. Long-term medical treatment is less frequently adopted. Recurrence in paediatric CD cases is low with factors predicting relapse being higher post-TSS cortisol and ACTH levels and rapid recovery of the hypothalamic-pituitary-adrenal axis after TSS. In summary, complete excision of the microadenoma with histological and biochemical evidence for this, predicts a low rate of recurrence of CD. Due to the need for rapid diagnosis and management to avoid the burden of prolonged exposure to hypercortisolism, tertiary university centres comprising both paediatric and adult endocrinology specialists together with experienced pituitary surgery and, eventually, radiotherapy units are recommended for referral of these patients.